#### Answer

$-3x^3$

#### Work Step by Step

$-7x^3 + 4x^3 = (-7+4)x^3 = -3x^3$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$-3x^3$

$-7x^3 + 4x^3 = (-7+4)x^3 = -3x^3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.